2017
DOI: 10.1002/joc.5106
|View full text |Cite
|
Sign up to set email alerts
|

The relation of cross‐equatorial flow during winter and spring with South China Sea summer monsoon onset

Abstract: ABSTRACT:The relationship between cross-equatorial flow (CEF) during winter and spring and the South China Sea summer monsoon (SCSSM) onset is investigated by data diagnoses for the period of 1979-2013 and numerical experiments. The SCSSM onset is found to have a significant negative correlation with the CEF nearby the Philippines in preceding January, February and March prior to SCSSM onset. A strong CEF during January, February and March tends to be succeeded by an early onset of SCSSM, whereas a weak CEF is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 33 publications
(38 reference statements)
1
23
0
Order By: Relevance
“…The onset of the SCSSM is accompanied by the "warm-in-north" and "cold-in-south" tropospheric temperature pattern surrounding the SCS, presenting the winter-to-summer seasonal transition of the meridional temperature gradient (MTG) in the middleupper troposphere (Mao et al, 2004b;Webster et al, 1998;Zhang et al, 2004). Except for the flourishing of monsoon convection over the SCS, the onset of the SCSSM includes the intrusion of the South Asian High (SAH) into the upper troposphere over the SCS , the eastward retreat of the western North Pacific subtropical high (WNPSH) in the middle-lower troposphere (Ding & Liu, 2001;He et al, 2017), and the generation of cross-equatorial flow south of Asia (Gao et al, 2012;Gao & Xue, 2006;Lin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The onset of the SCSSM is accompanied by the "warm-in-north" and "cold-in-south" tropospheric temperature pattern surrounding the SCS, presenting the winter-to-summer seasonal transition of the meridional temperature gradient (MTG) in the middleupper troposphere (Mao et al, 2004b;Webster et al, 1998;Zhang et al, 2004). Except for the flourishing of monsoon convection over the SCS, the onset of the SCSSM includes the intrusion of the South Asian High (SAH) into the upper troposphere over the SCS , the eastward retreat of the western North Pacific subtropical high (WNPSH) in the middle-lower troposphere (Ding & Liu, 2001;He et al, 2017), and the generation of cross-equatorial flow south of Asia (Gao et al, 2012;Gao & Xue, 2006;Lin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The variation of the SCSSM onset time has a broad impact on the East Asian weather and climate in boreal summer (Nitta 1987;Lin et al 2010) and the Indian Ocean climate variability (Kajikawa et al 2003). The onset date of SCSSM varies within large extent, for example, the difference between the earliest onset and the latest onset is more than 50 days during the years of 1979-2013 (Lin et al 2013(Lin et al , 2017. The mechanism about SCSSM onset appeals to a great deal of researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Feng and Hu (2014) deemed that the ocean heat content of upper 400 m layer in the region of (130°-150° E, 0-14° N) may be a predictor for SCSSM onset. Some studies showed that cold air originated from Southern Hemisphere through cross-equatorial flow impacts monsoon activity (Ramaswamy and Pareek 1978;Kuettner and Unninayar 1980;Sikka 1980;Rodwell 1996;He and Chen 1989;He et al 1991;Li and Wu 2002;Gao and Xue 2006;Lin et al 2017). The SCSSM onset exhibits significant interdecadal variation in addition to interannual variation.…”
Section: Introductionmentioning
confidence: 99%
“…A stronger SCSCEF would help to push the WNPSH to move northwards, thus favours an early SCSSMO (Gao and Xue, 2006). A recent study by Lin et al (2017) also reported that a strong CEF around the Philippines in preceding months (from January to March) is likely to be followed by an early SCSSMO.…”
mentioning
confidence: 99%